Patiromer Facilitates Angiotensin Inhibitor and Mineralocorticoid Antagonist Therapies in Patients With Heart Failure and Hyperkalemia - Pitt, Bertram; Anker, Stefan D; Lund, Lars H; Coats, Andrew J S; Filippatos, Gerasimos; Rossignol, Patrick; Weir, Matthew R; Friede, Tim; Kosiborod, Mikhail N; Metra, Marco; Böhm, Michael; Ezekowitz, Justin A; et al. (Journal of the American College of Cardiology, 2024)
BACKGROUND: Hyperkalemia (HK) is associated with suboptimal renin-angiotensin system (RAS) inhibitor and mineralocorticoid receptor antagonist (MRA) use in heart failure with reduced ejection fraction (HFrEF). OBJECTIVES: This study sought to assess characteristics and RAS inhibitor/MRA use in patients receiving patiromer during the DIAMOND (Patiromer for the Management of Hyperkalemia in Subjects Receiving RAASi Medications for the Treatment of Heart Failure) run-in phase. METHODS: Patients with HFrEF and HK or past HK entered a run-in phase of ≤12 weeks with patiromer-facilitated RAS inhibitor/MRA optimization to achieve ≥50% recommended RAS inhibitor dose, 50 mg/d MRA, and normokalemia. Patients achieving these criteria (randomized group) were compared with the run-in failure group (patients not meeting the randomization criteria). RESULTS: Of 1,038 patients completing the run-in, 878 (84.6%) were randomized and 160 (15.4%) were run-in failures. Overall, 422 (40.7%) had HK entering run-in with a similar frequency in the randomized and run-in failure groups (40.3% vs 42.5%; P = 0.605). From start to the end of run-in, in the randomized group, an increase was observed in target RAS inhibitor and MRA use in patients with HK (RAS inhibitor: 76.8% to 98.6%; MRA: 35.9% to 98.6%) and past HK (RAS inhibitor: 60.5% to 98.1%; MRA: 15.6% to 98.7%). Despite not meeting the randomization criteria, an increase after run-in was observed in the run-in failure group in target RAS inhibitor (52.5% to 70.6%) and MRA use (15.0% to 48.1%). This increase was observed in patients with HK (RAS inhibitor: 51.5% to 64.7%; MRA: 19.1% to 39.7%) and past HK (RAS inhibitor: 53.3% to 75.0%; MRA: 12.0% to 54.3%). CONCLUSIONS: In patients with HFrEF and HK or past HK receiving suboptimal RAS inhibitor/MRA therapy, RAS inhibitor/MRA optimization increased during patiromer-facilitated run-in.
Keywords: antagonisté mineralokortikoidních receptorů; tepový objem; Hyperkalemia; Angiotensin-Converting Enzyme Inhibitors; Humans; Heart Failure; Stroke Volume; srdeční selhání; lidé středního věku; hyperkalemia; mineralocorticoid receptor antagonists; Female; Aged; inhibitory ACE; renin–angiotensin system inhibitors; senioři; lidé; heart failure; polymery; Polymers; Mineralocorticoid Receptor Antagonists; ženské pohlaví; Male; Middle Aged; patiromer; Angiotensin Receptor Antagonists; hyperkalemie; Renin-Angiotensin System; mužské pohlaví; renin-angiotensin systém; antagonisté receptorů pro angiotenzin